Method for producing porous body
By using a polymerizable monomer with a specific functional group concentration and solvent vaporization, the method controls pore diameter to 1000 nm or less, addressing the limitations of existing methods and enabling suitable porous bodies for separation and porous membranes.
Patent Information
- Application Number
- JP2022181045
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-11-11
AI Technical Summary
Existing methods do not provide a means to control the pore diameter of porous bodies to 1000 nm or less, which is necessary for certain applications such as separation membranes and porous membranes.
A method involving the use of a polymerizable monomer with a specific functional group concentration, polymerization initiator, and solvent to form a phase-separated product, followed by solvent vaporization, allowing control of pore diameter to 1000 nm or less.
The method enables the production of porous bodies with pore diameters of 1000 nm or less, suitable for applications like separation membranes and porous membranes.
Smart Images

Figure 0007616192000002 
Figure 0007616192000003 
Figure 0007616192000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a porous body. [Background technology]
[0002] Polymeric porous bodies (hereinafter simply referred to as "porous bodies") are used, for example, in foams (e.g., cushioning materials, etc.), separation membranes (e.g., water treatment, etc.), porous membranes (e.g., battery separators, etc.), and reflective substrates (e.g., lighting fixtures, etc.).
[0003] Patent Document 1 discloses a method for forming a porous body. In the method disclosed in Patent Document 1, a composition containing a binder resin, a photosensitive compound, and a photopolymerization initiator is applied onto a substrate to form a coating film. Next, the coating film is irradiated with ultraviolet light according to a desired pattern using an ultra-high pressure mercury lamp. Next, the coating film is immersed in a poor solvent for the binder resin. Next, the poor solvent that has penetrated into the inside of the coating film is volatilized. This results in a porous body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-143427 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, Patent Document 1 does not disclose a method for controlling the pore size of the porous body. Depending on the application of the porous body (for example, separation membrane, porous membrane, etc.), a porous body with a pore size of 1000 nm or less is required.
[0006] The present disclosure has been made in consideration of the above circumstances. An object of one embodiment of the present disclosure is to provide a method for producing a porous body, which is capable of producing a porous body having a pore size of 1000 nm or less. [Means for solving the problem]
[0007] As a result of intensive research into the above-mentioned problems, the present inventors have experimentally found that the pore size of the resulting porous body can be controlled by using a polymerizable monomer whose functional group concentration, which is one of the factors that affect the polymerization rate, is within a specific range. Based on this finding, the present inventors have completed the present invention.
[0008] Means for solving the above problems include the following embodiments. <1> preparing a solution containing a polymerizable monomer having a functional group concentration of 3.0 mmol / g to 12.5 mmol / g, a polymerization initiator, and a solvent; activating the polymerization initiator contained in the solution to polymerize the polymerizable monomer, thereby forming a phase-separated product containing a porous body and the solvent from the solution; and vaporizing the solvent contained in the phase-separated product. <2> In adjusting the solution, the functional group concentration is 5.0 mmol / g or more. <1> A method for producing the porous body according to claim 1. <3> In preparing the solution, the content of the polymerizable monomer is 14% by mass to 44% by mass with respect to the total amount of the solution. <1> or <2> A method for producing the porous body according to claim 1. <4> In preparing the solution, the content of the polymerization initiator is 0.01% by mass to 3.00% by mass with respect to the total amount of the solution. <1> ~ <3> 13. A method for producing a porous body according to any one of the above items. <5> The pore size of the porous body is 500 nm or less. <1> ~ <4> 13. A method for producing a porous body according to any one of the above items. Effect of the Invention
[0009] According to the present disclosure, there is provided a method for producing a porous body, which is capable of producing a porous body having a pore size of 1000 nm or less. [Brief description of the drawings]
[0010] [Figure 1] 1 is a scanning electron microscope (SEM) photograph (magnification: 50,000 times) of the surface of the porous body of the example. 1A is Comparative Example 1 (functional group concentration: 2.9 mmol / g), 1B is Example 1 (functional group concentration: 6.7 mmol / g), and 1C is Example 2 (functional group concentration: 7.0 mmol / g). [Diagram 2] 2 is a SEM photograph (magnification: 50,000 times) of the surface of the porous body of the example. 2A is Example 3 (functional group concentration: 8.6 mmol / g), 2B is Example 4 (functional group concentration: 10.5 mmol / g), and 2C is Example 5 (functional group concentration: 11.5 mmol / g). [Diagram 3] FIG. 3 is an SEM photograph (magnification: 50,000 times) of the surface of the porous body of Example 6 (functional group concentration: 11.8 mmol / g). [Figure 4] 4 is an SEM photograph (magnification: 50,000 times) of the surface of the porous body of the example. 4A is Example 4 (solvent: diethylene glycol diethyl ether), and 4B is Example 7 (solvent: 2-ethoxyethanol). [Diagram 5] 5 is a SEM photograph (magnification: 50,000 times) of the surface of the porous body of the example. 5A is Example 8 (monomer concentration: 9 mass%), 5B is Example 9 (monomer concentration: 19 mass%), 5C is Example 1 (monomer concentration: 29 mass%), and 5D is Example 10 (monomer concentration: 39 mass%). [Figure 6] 6 is an SEM photograph (magnification: 50,000 times) of the surface of the porous body of the example. 6A is Example 11 (polymerization initiator concentration: 0.01 mass%), 6B is Example 1 (polymerization initiator concentration: 1 mass%), and 6C is Example 12 (polymerization initiator concentration: 5 mass%). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present disclosure, a numerical range indicated using "~" means a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in the present disclosure, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described in stages. In the numerical ranges described in the present disclosure, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the Examples. In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, the amount of each component means the total amount of the multiple substances unless otherwise specified, when there are multiple substances corresponding to each component. In the present disclosure, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In the present disclosure, "(meth)acrylate" refers to at least one of acrylate and methacrylate, and "(meth)acryloyl group" refers to at least one of acryloyl group and methacryloyl group.
[0012] (1) Method for producing porous body The method for producing a porous body according to the present disclosure includes preparing a solution containing a polymerizable monomer having a functional group concentration of 3.0 mmol / g to 12.5 mmol / g (hereinafter also referred to as simply "polymerizable monomer"), a polymerization initiator, and a solvent (hereinafter also referred to as the "preparation step"); activating the polymerization initiator contained in the solution and polymerizing the polymerizable monomer to form a porous body having a pore size of 1000 nm or less and a phase-separated product containing the solvent from the solution (hereinafter also referred to as the "formation step"); and vaporizing the solvent contained in the phase-separated product (hereinafter also referred to as the "vaporization step").
[0013] The term "polymerizable monomer" refers to a monomer containing an ethylenically unsaturated group. The term "functional group concentration" refers to a value calculated from the following formula (a). Formula (a): Functional group concentration [mmol / g] = (average number of functional groups contained in polymerizable monomer [mol] / average molecular weight (Mw) of polymerizable monomer [g]) × 1000 [mmol / mol] "Average number of functional groups" refers to the average number of functional groups (i.e., ethylenically unsaturated groups) per molecule, and when three types of polymerizable monomers are included, it is the average number of the three numbers. When the polymerizable monomer is a (meth)acrylate having a (meth)acryloyl group, the functional group indicates a (meth)acryloyl group. "Average molecular weight" refers to the average molecular weight of all polymerizable monomers, and is calculated by arithmetic calculation. "Activating a polymerization initiator" refers to generating active species such as radicals by irradiating the polymerization initiator with active energy rays (e.g., electromagnetic waves, radiation, etc.). "Solution" refers to a liquid phase in which the two are homogeneously dissolved. "Porous body" refers to a polymer (solid phase) of a polymerizable monomer.
[0014] The method for producing a porous body according to the present disclosure has the above-mentioned configuration, and therefore can produce a porous body having a pore size of 1000 nm or less.
[0015] (1.1) Preparation process In the adjusting step, a solution containing a polymerizable monomer having a functional group concentration of 3.0 mmol / g to 12.5 mmol / g, a polymerization initiator, and a solvent is prepared.
[0016] The solution contains a polymerizable monomer. The polymerizable monomer preferably has a (meth)acryloyl group. Examples of the polymerizable monomer having a functional group concentration of 3.0 mmol / g to 12.5 mmol / g include monofunctional polymerizable monomers, bifunctional polymerizable monomers, and trifunctional or higher polymerizable monomers. Examples of the monofunctional polymerizable monomer include β-carboxyethyl (meth)acrylate (functional group concentration: 6.9 mmol / g), isobornyl (meth)acrylate (functional group concentration: 4.8 mmol / g), and ethoxylated phenyl (meth)acrylate (functional group concentration: 4.2 mmol / g). Examples of bifunctional polymerizable monomers include tricyclodecane dimethanol di(meth)acrylate (functional group concentration: 6.7 mmol / g), ethylene oxide (EO)-modified neopentyl glycol di(meth)acrylate (EBECRYL 150) (functional group concentration: 3.9 mmol / g), dipropylene glycol di(meth)acrylate (functional group concentration: 8.2 mmol / g), and glycerin di(meth)acrylate (functional group concentration: 10.0 mmol / g). Examples of trifunctional or higher polymerizable monomers include pentaerythritol ethoxy tetra(meth)acrylate (functional group concentration: 7.0 mmol / g), ditrimethylolpropane tetra(meth)acrylate (functional group concentration: 8.6 mmol / g), trimethylolpropane tri(meth)acrylate (functional group concentration: 10.5 mmol / g), dipentaerythritol hexa(meth)acrylate (functional group concentration: 11.5 mmol / g), and glycerin tri(meth)acrylate (functional group concentration: 11.8 mmol / g). The polymerizable monomer may be one type alone or two or more types in combination. The functional group concentration in the examples of the polymerizable monomer is the functional group concentration when the (meth)acrylate is an acrylate. When the porous body is used as a separator for a lithium secondary battery using a non-aqueous electrolyte (hereinafter also simply referred to as "separator"), the polymerizable monomer is preferably a polymerizable monomer that does not contain an ether bond.
[0017] The functional group concentration of the polymerizable monomer is preferably 0.50 or more. This makes it possible to obtain a porous body having a pore diameter of 10 nm to 500 nm and a porosity of 40% or more. When the porosity is 40% or more, the porous body functions as a separator (hereinafter, also simply referred to as "separator") for a lithium secondary battery using a non-aqueous electrolyte. Therefore, the obtained porous body is suitable for use as a separator. From the viewpoint of making the pore diameter smaller, the functional group concentration of the polymerizable monomer is more preferably 0.75 to 1.25, and even more preferably 0.95 to 1.25.
[0018] The content of the polymerizable monomer is not particularly limited, but is preferably 14% by mass to 44% by mass based on the total amount of the solution. This makes it possible to obtain a porous body suitable for a separator. From the viewpoint of keeping the pore diameter small and the porosity high, the content of the polymerizable monomer is more preferably 24% by mass to 39% by mass.
[0019] The solution contains a polymerization initiator. Examples of the polymerization initiator include a photopolymerization initiator that generates active species such as radicals by irradiation with active energy rays (e.g., electromagnetic waves, radiation, etc.), and a thermal polymerization initiator that generates active species such as radicals by applying heat, and the photopolymerization initiator is preferable. Examples of the photopolymerization initiator include an acetophenone-based compound (e.g., 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-1,2-diphenylethan-1-one, etc.), a benzophenone-based compound (e.g., benzophenone, 4-phenylbenzophenone, etc.), and the like. The polymerization initiator may be used alone or in combination of two or more types.
[0020] The content of the polymerization initiator is not particularly limited, and is preferably 0.01% by mass to 3.00% by mass with respect to the total amount of the solution. This makes it possible to obtain a porous body having a pore size of 10 nm to 500 nm and a porosity of 50% or more. If the porosity is 50% or more, the battery performance of the nonaqueous electrolyte secondary battery becomes less dependent on the porosity. In other words, the battery performance of the nonaqueous electrolyte secondary battery is improved.
[0021] The solution contains a solvent. Examples of the solvent include ether solvents (e.g., diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 2-methoxyethanol, 2-ethoxyethanol, ethyl ether, n-butyl ether, n-hexyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol monophenyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, triethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, 1,4-dioxane, etc.), polyhydric alcohol solvents (e.g., ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 1,2-hexanediol, etc.), ester solvents (e.g., diethyl carbonate, methyl acetate, ethyl acetate, etc.), etc. The solvent may be used alone or in combination of two or more kinds.
[0022] Among them, the solvent preferably contains an ether-based solvent, and more preferably consists of an ether-based solvent, so that the structure of the obtained porous body tends to be a structure in which each of the multiple particulate materials is connected to each other. Furthermore, when the solvent contains an ether solvent, the polymerizable monomer having a functional group concentration of 3.0 mmol / g to 12.5 mmol / g preferably contains a difunctional or higher functional polymerizable monomer, which results in a porous body with a smaller pore size.
[0023] The solution may or may not contain additives, such as dispersants, adhesion promoters such as silane coupling agents, antioxidants, anti-aggregation agents, antifoaming agents, and surfactants.
[0024] (1.2) Formation process In the forming step, the polymerization initiator contained in the solution is activated to polymerize the polymerizable monomer, thereby forming a phase-separated product containing a porous body and the solvent from the solution.
[0025] The method for activating the polymerization initiator is not particularly limited, and examples thereof include a method of irradiating the solution with electromagnetic waves (far ultraviolet rays, ultraviolet rays, near ultraviolet rays, etc.) and radiation (e.g., electron beams, X-rays, gamma rays, etc.). Among these, the method for activating the polymerization initiator is preferably irradiation with ultraviolet rays. The intensity of the ultraviolet rays is preferably 5 mW / cm. 2 ~800mW / cm 2 , more preferably 30 mW / cm 2 ~250mW / cm 2 The temperature of the solution during irradiation with ultraviolet rays is preferably 25° C. to 120° C., more preferably 25° C. to 60° C. When activating the polymerization initiator, the solution may be in the form of a coating film applied onto the surface of the substrate.
[0026] (1.3) Vaporization process In the vaporization step, the solvent contained in the phase-separated product is vaporized.
[0027] The method for vaporizing the solvent is not particularly limited, and examples thereof include heat drying, reduced pressure drying, freeze drying, etc. In heat drying, if the heating temperature is equal to or lower than the glass transition temperature of the polymerizable monomer or its polymer, the solvent can be removed from the phase-separated product without destroying the porous structure of the porous body. Examples of heat drying include radiant heat drying using an infrared heater and air drying using a blower.
[0028] (1.4) Porous bodies The porous body obtained by the method for producing a porous body according to the present disclosure has a porosity of 1000 μm or less.
[0029] The size of the porous body is not particularly limited and is appropriately selected according to the application of the porous body. For example, the porous body is preferably used for foams (e.g., cushioning materials, etc.), separation membranes (e.g., water treatment, etc.), porous membranes (e.g., separators, etc.), and reflective substrates (e.g., lighting fixtures, etc.).
[0030] The pore size of the porous body is preferably 500 nm or less, which makes the porous body suitable for use as a separator. EXAMPLES
[0031] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.
[0032] [1] Porous membrane [1.1] Example 1 [1.1.1] Preparation process Tricyclodecane dimethanol diacrylate was prepared as a polymerizable monomer. Based on the values listed in the catalog of the polymerizable monomer (number of functional groups: 2, average molecular weight (Mw): 300), the functional group concentration of the polymerizable monomer was 6.7 mmol / g. Diethylene glycol diethyl ether was prepared as a solvent. 1-Hydroxycyclohexyl phenyl ketone was prepared as a polymerization initiator. 29 parts by mass of the polymerizable monomer was placed in a sample bottle, and then 70 parts by mass of the solvent and 1 part by mass of the polymerization initiator were added. The mixture was stirred until the polymerizable monomer and the polymerization initiator were completely dissolved in the solvent to obtain a solution.
[0033] [1.1.2] Forming process The inside of the glove box was purged with nitrogen gas (N2). The oxygen gas concentration in the glove box was 0%. In this glove box, the solution was applied to a copper foil by casting to form a coating film. The thickness of the coating film was 120 μm. The coating film was irradiated with ultraviolet (UV) rays to obtain an irradiated coating film. A UV irradiation device was used for the UV irradiation. The UV irradiation time was 60 seconds, and the UV irradiation intensity was 50 mW / cm. 2 The temperature of the coating film during UV irradiation was 25°C.
[0034] [1.1.3] Vaporization process The copper foil on which the irradiated coating film was formed was placed on a hot plate. The hot plate was set at a temperature of 120° C., and the irradiated coating film was heated at 120° C. for 5 minutes to volatilize and remove the solvent from the irradiated coating film. This resulted in a polymer film.
[0035] The surface of the polymer film was observed using a scanning electron microscope (SEM) (magnification: 10,000 times or 50,000 times). FIG. 1 shows an SEM image of the polymer film of Example 1.
[0036] [1.2] Examples 2 to 6 and Comparative Example 1 Polymer films were obtained in the same manner as in Example 1, except that the type of polymerizable monomer was changed as shown in Table 1. Fig. 1 shows SEM images of the polymer films of Examples 2 to 6 and Comparative Example 1. The functional group concentrations of the polymerizable monomers were calculated using the values listed in the catalogs of the polymerizable monomers, as in Example 1. Figs. 1 to 3 show SEM images of the polymer films of Examples 2 to 6.
[0037] [1.3] Example 7 Polymer membranes were obtained in the same manner as in Example 4, except that the type of solvent was changed as shown in Table 1. Fig. 4 shows SEM images (magnification: 50,000 times) of the polymer membranes of Examples 4 and 7.
[0038] [1.4] Examples 8 to 10 Polymer films were obtained in the same manner as in Example 1, except that the content of the polymerizable monomer was changed as shown in Table 1. Fig. 5 shows SEM images (magnification: 50,000 times) of the polymer films of Examples 1 and 8 to 10.
[0039] [1.5] Examples 11 and 12 Polymer films were obtained in the same manner as in Example 1, except that the content of the polymerization initiator was changed as shown in Table 1. Fig. 6 shows SEM images (magnification: 50,000 times) of the polymer films of Examples 1, 11, and 12.
[0040] [2] Evaluation method [2.1] Porosity measurement The polymer membrane was punched out to a predetermined size to prepare a sample membrane. The mass, area and thickness of this sample membrane were measured. The apparent density was calculated from the measured values of the mass, area and thickness of the sample membrane according to the following formula (a). The porosity of the sample membrane was calculated from the true density of the polymer constituting the polymer membrane according to the following formula (b). The calculated porosity of the sample membrane was taken as the porosity of the polymer membrane. The results are shown in Table 1. Formula (a): Apparent density = mass of sample film / (area of sample film x film thickness of sample film) Equation (b): Porosity of sample membrane = [1-(apparent density / true density)] x 100
[0041] [2.2] Porosity evaluation Based on the porosity calculation results, the porosity of the polymer membrane was evaluated according to the following criteria: An acceptable porosity evaluation result is "A". "A": The porosity of the polymer membrane is 40% or more. "B": The porosity of the polymer membrane is less than 40%. "A" means that the polymer membrane is evaluated as porous. "B" means that the polymer membrane is not porous. Hereinafter, polymer membranes with a porosity evaluation result of "A" will also be referred to as "porous membranes."
[0042] [2.3] Pore size measurement The shape of the porous membrane was observed using a field emission scanning electron microscope (FE-SEM) ("JSM-7100F" manufactured by JEOL Ltd.). The porous membrane was coated with platinum (Pt) to prevent charging of the porous membrane. The cross section of the porous membrane was observed. The cross section of the porous membrane was a fracture surface of the porous membrane obtained by breaking the porous membrane using liquid nitrogen. The diameters of multiple pores in the captured surface SEM image were measured. The average value of the measured diameters of multiple pores was taken as the pore diameter. The measurement results are shown in Table 1. The allowable range of pore diameters is 1000 nm or less.
[0043] [Table 1]
[0044] In Table 1, in the section on polymerizable monomers, "PEGDA" refers to PEG600 diacrylate. "TCDDA" refers to tricyclodecane dimethanol diacrylate. "PEEOTA" refers to pentaerythritol ethoxy tetraacrylate. "Di-TMPTA" refers to ditrimethylolpropane tetraacrylate. "TMPTA" refers to trimethylolpropane triacrylate. "DPHA" refers to dipentaerythritol hexaacrylate. "GLYTA" refers to glycerin triacrylate. In the section on polymerization initiators, "HPK" refers to 1-hydroxycyclohexyl phenyl ketone. In the section on solvents, "DEDE" refers to diethylene glycol diethyl ether. "DMAc" refers to dimethylacetamide. "2EE" refers to 2-ethoxyethanol.
[0045] In the manufacturing method of Comparative Example 1, the functional group concentration of the polymerizable monomer was 2.9 mmol / g, which was not within the range of 3.0 mmol / g to 1.25 mmol / g. Therefore, the porosity evaluation of Comparative Example 1 was "B." In other words, as shown in FIG. 1A, the polymer membrane of Comparative Example 1 was not porous. As a result, it was found that the manufacturing method of Comparative Example 1 is not a manufacturing method capable of manufacturing a porous membrane with a pore diameter of 1000 μm or less.
[0046] The manufacturing methods of Examples 1 to 12 included a preparation step, a formation step, and a vaporization step, and the functional group concentration of the polymerizable monomer was in the range of 3.0 mmol / g to 1.25 mmol / g. Therefore, the pore diameters of Examples 1 to 12 were 570 nm or less. Furthermore, as shown in 1B and 1C in FIG. 1 and in FIGS. 2 to 6, the polymer membranes of Examples 1 to 12 were porous. As a result, it was found that the manufacturing methods of Examples 1 to 12 were capable of manufacturing porous membranes with pore diameters of 1000 μm or less. Furthermore, as shown in 1B and 1C in FIG. 1 and in FIGS. 2 to 6, it was found that the porous bodies of Examples 1 to 12 had a structure in which a plurality of particulate materials were each connected to one another.
Claims
1. preparing a solution containing a polymerizable monomer having a functional group concentration of 10.5 mmol / g to 12.5 mmol / g, a polymerization initiator, and a solvent; applying the solution onto a copper foil, activating the polymerization initiator contained in the solution, and polymerizing the polymerizable monomer to form a phase-separated product containing a porous body and the solvent from the solution; and evaporating the solvent contained in the phase separated product; In preparing the solution, a content of the polymerizable monomer is 14% by mass to 44% by mass, and a content of the polymerization initiator is 0.01% by mass to 3.00% by mass, based on a total amount of the solution.
2. The method for producing a porous body according to claim 1 , wherein the pore size of the porous body is 500 nm or less.
Citation Information
Patent Citations
Film type printing paper
JP2002178630A
Recording paper and manufacturing method therefor
JP2003191628A
Photopolymerizable composition for forming porous pattern, method for forming the porous pattern by using the same and the porous pattern
JP2004143427A
Release film for the production of polyimide film
JP2019059050A
Method for producing porous layer, porous layer, and electrode
JP2020070362A